Oral Microbiota Dysbiosis in Firefighters and the Potential Contributing Environmental and Lifestyle Factors Based on a Case-Control Study - Sukanta S. Bhattacharya; Brijesh Yadav; Roman Jandarov; William A. Jetter; Jagjit S. Yadav (Microorganisms)
Epidemiological studies show firefighters have increased risks of cancer, diabetes, and cardiovascular disease. To explore links between occupational/environmental exposures and dysbiosis-associated health risks, this case-control study compared oral microbiota of age-matched firefighters (n = 13) and non-firefighters (n = 13) using next-generation sequencing. Firefighters exhibited significantly reduced overall microbial diversity (p ≤ 0.05) and compositional shifts. Firmicutes increased from 53.5% to 68.5%, and Bacteroidetes from 9.5% to 14.1%, while Proteobacteria decreased from 24.6% to 8.3%, and Fusobacteria from 3.3% to 1.1%. This resulted in a higher Firmicutes to Bacteroidetes ratio (5.63 vs. 4.89 in controls), indicating a pro-inflammatory oral microenvironment. At the family level, Streptococcaceae (45.1% to 60.3%) and Prevotellaceae (6.2% to 10.0%) increased, whereas Neisseriaceae (17.7% to 4.9%) and Fusobacteriaceae (2.1% to 0.8%) decreased. The genus Streptococcus dominated firefighters’ microbiota, rising from 45.1% to 60.3%. Diversity indices confirmed reduced microbial evenness and richness in firefighters. Metadata analysis linked frequent fire exposures to perturbations in Comamonadaceae and Carnobacteriaceae (p ≤ 0.05). Barbecue consumption, a source of polycyclic aromatic hydrocarbons, correlated with elevated Spirochaetaceae and Peptostreptococcaceae. This first report on oral dysbiosis in firefighters reveals significant alterations in microbiota abundance, diversity, and evenness, implying potential health risks for this group.